1982
DOI: 10.1677/joe.0.0920425
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Single Injections of Bovine Follicular Fluid on Gonadotrophin Concentrations Throughout the Oestrous Cycle of the Rat

Abstract: A single injection of steroid-free bovine follicular fluid (bFF), which contains inhibin-like activity, was given to adult female rats at 09.00 h on dioestrus-2 (the day after metoestrus), dioestrus-3, pro-oestrus or oestrus. peripheral concentrations of gonadotrophins were measured at 2-h intervals after injection. Compared with values in control animals treated with bovine plasma, injection of bFF did not influence concentrations of LH. In contrast, at all days studied injection of bFF resulted in suppressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1984
1984
1989
1989

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…It is remarkable that around the same time (after day -6) serum FSH reaches levels equal to or below 200 pg/1 with much less ( <005) fluctuation than during the preceding period. Thus, a situation comparable to that during the adult cycle, with relatively low FSH con¬ centrations ( 200 pg/1) varying within narrow limits (Hermans, Debets, van Leeuwen & de Jong, 1982a), then develops for the first time at this stage in pubertal rats. This strongly suggests that ovarian ILA plays a role in the fine regulation of serum FSH during these last 5 days preceding first ovulation.…”
Section: Discussionmentioning
confidence: 84%
“…It is remarkable that around the same time (after day -6) serum FSH reaches levels equal to or below 200 pg/1 with much less ( <005) fluctuation than during the preceding period. Thus, a situation comparable to that during the adult cycle, with relatively low FSH con¬ centrations ( 200 pg/1) varying within narrow limits (Hermans, Debets, van Leeuwen & de Jong, 1982a), then develops for the first time at this stage in pubertal rats. This strongly suggests that ovarian ILA plays a role in the fine regulation of serum FSH during these last 5 days preceding first ovulation.…”
Section: Discussionmentioning
confidence: 84%
“…There are reports indicating that the administration of follicular fluid during the normal ovarian cycle in rats suppresses the proestrus as well as the estrus FSH surge [12] and also affects follicular growth and ovulation [13]. In contrast to these findings, DePaolo and colleagues [14] and Nandedkar and colleagues [15] observed that inhibin did not affect ovulation in cyclic rats, nor did it alter oocyte maturation or ovarian morphology.…”
Section: Effect Of Inhibin On Ovulation and Implantationmentioning
confidence: 98%
“…Moreover, in the adult cyclic rat a relationship exists between the phase of the oestrous cycle and peripheral levels of FSH (see Nequin, Alvarez & Schwartz, 1979, for references), between the phase of the oestrous cycle and steroid and inhibin levels in ovarian venous plasma (OVP) (DePaolo, Shander, Wise et al 1979) and in follicular fluid (Fujii, Hoover & Channing, 1983) and, more directly, between fluctuations in the levels of FSH and inhibin (DePaolo, Anderson & Hirshfield, 1981;Hermans, Debets, van Leeuwen & de Jong, 1981, 1982a. It is therefore tempting to postulate that there is a closed feedback system between FSH and inhibin which plays a role in the regulation of the oestrous cycle and follicular growth.…”
mentioning
confidence: 99%